Pola Komunikasi Terapeutik Pengasuh Dengan Lansia di Sentra Terpadu Pangudi Luhur Kemensos Bekasi - Winda Primasari; Aulia Zahra Oktavia (WACANA: Jurnal Ilmiah Ilmu Komunikasi, 2026)
Therapeutic communication is a specific form of communication practised by healthcare professionals, particularly nurses, with the aim of helping patients understand their condition and alleviating the mental and emotional strain they experience. Therapeutic communication involves efforts made by caregivers when communicating with older people who have physical and psychological limitations. The aim of this study is to examine the patterns of therapeutic communication between carers and older adults, as well as the barriers faced by carers at the Pangudi Luhur Integrated Centre of the Ministry of Social Affairs in Bekasi. This study employs a descriptive qualitative method. Data collection was carried out through in-depth interviews and observation at the Pangudi Luhur Integrated Centre of the Ministry of Social Affairs in Bekasi. The informants in this study were four caregivers who interact with the elderly daily. The key informants in this study were a geriatric nurse, a care assistant, and three elderly residents at the Pangudi Luhur Integrated Centre of the Ministry of Social Affairs in Bekasi. The results of the study indicate that therapeutic communication between carers and the elderly is proceeding well. A new finding in this study is the PRIM therapeutic communication pattern (persuasion, repetition, instruction and motivation). The PRIM communication approach adopted by these carers can improve the quality of life of the elderly.